Quantification of Circulating Epstein-Barr Virus Latent Membrane Protein 1 Gene and Analysis Of 30-Bp Deletion and Xhoi-Loss Variants in Nasopharyngeal Carcinoma - See, Hui Shien (2007)
Nasopharyngeal carcinoma (NPC) is a human epithelial tumour with a high prevalence in Southern Chinese population. In Malaysia, NPC has become the second most frequent cancers among males and fifth most frequent cancers in females. Genetics, immunologic factors, preserved foods, excessive salts, smoking, various infecting factors are relevant with NPC. A unique feature of NPC is its strong association with Epstein-Barr virus (EBV). Previous studies have shown that EBV-encoded latent membrane protein 1 (LMP1) gene was considered to be associated with the tumourigenesis of NPC. The presence of EBV LMP1 gene variants were shown to be more oncogenic than the LMP1 gene from the prototype virus, B95-8. Free EBV DNA can be detected in serum or plasma from NPC patients and it has been shown to be derived from tumours. This raises the possibility that an easy and non-invasive method may be developed for diagnostic and disease monitoring purposes in NPC. Thus, the aim of the study is to determine the prevalence of these variants, based mainly on the XhoI restriction site polymorphism and the 30bp deletion of LMP1 gene, and to evaluate the potential role of circulating EBV LMP1 as a molecular marker for diagnosis and disease monitoring in NPC patients. By employing Polymerase Chain Reaction method (PCR), the presence of 30bp deletion and the loss of XhoI restriction site of LMP1 gene in 42 and 10 archival formalin fixed, paraffin-embedded tissues of NPC and non-malignant nasopharyngeal biopsy specimens, respectively, and 35 plasma samples from nasopharyngeal carcinoma were studied. The wild type EBV strain from B95.8 was used as negative control and DNA from 2 NPC tissues as confirmed by DNA sequencing for the presence of 30-bp deletion was used as the positive control in this study. In the quantification of circulating EBV DNA load analysis, 41 plasma samples from NPC patients were used. Standard curve generated by using quantitative Real-Time PCR method against EBV LMP1 was used to quantify the circulating EBV DNA in 18 NPC subjects at the time of the initial diagnosis, 14 in the middle of treatment and 9 after radiotherapy or chemotherapy. The EBV DNA copy number in 19 apparently healthy adults was also evaluated. The results showed that: 1) The presence of 30-bp deletion and loss of XhoI restriction site can be found in both nasopharyngeal biopsy tissues and also in plasma samples. However, the frequency detected in plasma was lower compared to primary tumour site. The 30-bp deletion was detected in 55.9% of NPC tissues and 24.1% NPC plasma. Interestingly, 17.2% of plasma samples harboured both the deleted and non-deleted variants, thus, suggestive of dual infections in these patients. The loss of XhoI restriction site in LMP1 gene was found in 87.2 % of the NPC tissues and 36.7% of plasma samples. There was no 30-bp deletion and XhoI-loss in non-malignant nasopharyngeal tissues. Majority of our samples (59.4% of NPC tissues and 26.9% of plasma samples) showed the presence of both of the 30-bp deletion and the loss of XhoI restriction site, which resembles the CAO, C1510, China 1 and DV2 isolated from high endemic area for NPC. 2) The 30-bp deletion and loss of XhoI restriction site have been found to be more prevalent in Chinese compared to Malay (30bp-deletion, p=0.000; XhoI-loss, p=0.046), and its percentage were higher in type III (undifferentiated carcinoma) than in type I (squamous cell carcinoma) NPC biopsy tissues (30bp-deletion, p=0.011; XhoI-loss, p=0.006). 3) The EBV DNA detection rate in the plasma of NPC patients (94.4%) was significantly higher than in apparently healthy adults (AHAs) (15.8%). According to the receiver-operating characteristic (ROC) curve analysis, plasma EBV DNA levels at the cut-off of 0 copy/ml combined a sensitivity of 94.4% (C.I.95%=72.6-99.1) with a specificity of 84.2% (C.I.95%=60.4-96.4) for detection of NPC, and a ROC AUC of 0.904 (C.I.95%: from 0.760-0.975). The mean circulating EBV DNA load in the plasma of untreated NPC patients (median=2471 copies/ml copies/ml) was higher than AHAs (median=0 copy/ml). A significant decrease in EBV load was observed in patients who had undergone radiotherapy (median=0 copy/ml) while three patients had remaining EBV load. The mean of the post-treatment EBV DNA levels were not statistically different with the AHAs samples. 4) None of the clinicopathological features were associated with the pretreatment plasma EBV DNA load including tumour histological type and clinical stage. The important findings in this study are: 1) High frequency of 30-bp deletion and XhoI-loss in the LMP1 gene is present in Malaysian NPC population. The distribution of higher level of 30-bp deletion and XhoI-loss in Chinese and Type III NPC may be associated with geographical/ethnic and clinical background. It suggested that these variants may have unique functional properties, which determine disease association or development. 2) The circulating EBV LMP1 was detectable in NPC patients and it was shown to be proportionally related to the presence of malignant disease, suggested that the LMP1 may serve as a molecular marker for diagnosis and disease monitoring in NPC. In conclusion, a high prevalence of 30-bp deletion and XhoI-loss in LMP1 were present in Malaysian NPC. By using the sensitive, accurate and robust real-time PCR technique, we have showed the clinical significance of detecting the EBV LMP1 in the plasma where the quantification of EBV LMP1 may be a useful indicator for screening, diagnosis and disease monitoring in NPC.